2015
DOI: 10.3746/jkfn.2015.44.7.1072
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous Chlorine Dioxide Treatment to Produce High Quality Paprika for Export

Abstract: To maintain high quality and microbiological safety of paprika during storage for export, paprika samples after harvest were treated with 75 ppmv chlorine dioxide (ClO2) gas and stored at 8°C, which is the optimal storage temperature, for 30 days. ClO2 gas treatment reduced initial populations of total aerobic bacteria in samples by 1.62 log CFU/g as well as yeast and molds by 1.45 log CFU/g compared to those of the control. During storage, weight loss of all samples increased, and samples treated with ClO2 ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
1
2
0
1
Order By: Relevance
“…Therefore, ClO 2 fumigation is expected to have a positive effect on the storage quality of Cheongdobansi by preserving its hardness, a major factor in evaluating the storage quality of fresh persimmons (Kim, 1999). Similar results were found in the studies of Choi et al (2013) and Kang et al (2015), in which ClO 2 gas treatment maintained the hardness of cherry https://doi.org/10.11002/kjfp.2023.30.2.190 tomatoes and paprika.…”
Section: Hardnesssupporting
confidence: 64%
See 1 more Smart Citation
“…Therefore, ClO 2 fumigation is expected to have a positive effect on the storage quality of Cheongdobansi by preserving its hardness, a major factor in evaluating the storage quality of fresh persimmons (Kim, 1999). Similar results were found in the studies of Choi et al (2013) and Kang et al (2015), in which ClO 2 gas treatment maintained the hardness of cherry https://doi.org/10.11002/kjfp.2023.30.2.190 tomatoes and paprika.…”
Section: Hardnesssupporting
confidence: 64%
“…ClO 2 gas has been used to enhance the storage quality of fruits such as tomatoes (Yang et al, 2020), strawberries (Kim and Hwang, 2019), paprika (Kang et al, 2015), and broccoli (Park and Lee, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Gaseous Chlorine Dioxide Treatment Suppresses Decay and Microbial Growth in Cold-stored Jujube Fruit of 80% to suppress decay and microbial growth (Kang et al, 2015;Kim and Song, 2017). A ClO2 generator (CA-300, Purgofarm Inc., Hwaseong, Korea) was used employing the electrochemical method reported by Gates (1998), in which highly pure ClO 2 gas produced by aqueous sodium chlorite was passed through a multi-porous membrane electrode assembly.…”
Section: Gaseous Clo 2 Fumigation Treatmentmentioning
confidence: 99%
“…Kang et al(34) reported that the color values of paprika were measured as L value of 30.75, a value of 23.27, b value of 11.38. Ha et al (35) investigated the effect of shading method on growth and fruit characteristics when harvesting paprika during summer and reported that the color values of paprika outside were measured as L value of 36.4, a value of 34.3, b value of 18.9.…”
mentioning
confidence: 99%